The Effects of digital technology adoption on organizational performance – a case study of Wellcome Trust Programme - Abud, M. (Strathmore University, 2025)
Digital transformation is reshaping the global landscape, driving innovation, enhancing lives, and creating interconnected systems. While digital technologies such as augmented reality, social media, artificial intelligence, big data, and the Internet of Things offer new business opportunities, create new business models and enhance customer experiences, many organizations struggle to fully harness their potential. Despite the potential for significant gains in innovation and operational efficiency through digital technology adoption, many organizations struggle to fully realize these benefits. This raises the key question of what drives digital technology adoption and how organizations can prioritize impactful, sustainable initiatives to enhance performance. This study examined the impact of digital technology adoption on organizational performance at Wellcome Trust Programme. Specifically, it explored the impact of enhanced communication collaboration, skill acquisition, digitized change management approaches, and data-driven decision-making on performance. The research is grounded in the Technology Acceptance Model, Innovation Diffusion Theory, and the Baldrige Performance Excellence Framework. This study adopted a positivist research philosophy and descriptive design, targeting a population of 760 staff members at the Wellcome Trust Programme, with a sample size of 263 determined using Yaman’s formula. Questionnaires served as the primary data collection tool, and analysis was conducted using SPSS for descriptive statistics, along with inferential analysis such as correlation, regression, and ANOVA. The research aimed to deepen understanding of the drivers of digital technology adoption and their impact on organizational performance. It addresses a critical gap between firms leveraging digitalization for competitive advantage and those struggling to realize its benefits. Notably, the study found that digital technology adoption accounts for 26.2% of variations in organizational performance at Wellcome Trust Programme and concludes that a significant positive relationship between digital technology adoption and organizational performance exists. The study recommends that Wellcome Trust Programme should align skill acquisition initiatives with targeted, impactful training, assess and address skill gaps, and motivate continuous learning. The organization should integrate digital tools and structured change management processes to streamline transitions, and empower employees to achieve intended business objectives. The programme should invest in data analytics tools, infrastructure, and governance to enable data-driven decision-making. Additionally, the leadership team should develop digital leadership capabilities to navigate emerging technologies and align strategies with digital trends. Finally, fostering a culture of open communication and collaboration through use of technology platforms and inclusive decision-making will create an empowered and cohesive workforce. Key Words: Digital transformation, Technology adoption, Organizational performance, Data-Driven Decision-Making
Full - text thesis